Analisis Profitabilitas Dan Pertumbuhan Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Moderasi Terhadap Nilai Perusahaan - Anissa Hafidza Pristi; Muhadjir Anwar (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of profitability and company growth with dividend policy as a moderating variable on the value of manufacturing companies in the food and beverage sector listed on the Indonesian stock exchange for 2017 – 2020 period. The research method used is causal research, the sample used is 18 companies, and analyzed with moderated regression analysis. The results of this study, are Profitability has a significant positive effect on Food and Beverage Company Value, Company Growth has no significant effect on Food and Beverage Company Value, Dividend Policy can weaken the influence of Profitability on Company Value, and Dividend Policy does not have a significant effect on Company Growth on The value of the company.